Characterization of Coffea arabica monofloral honey from Espírito Santo, Brazil - Kadri, Samir Moura [UNESP]; Zaluski, Rodrigo [UNESP]; Pereira Lima, Giuseppina Pace [UNESP]; Mazzafera, Paulo; De Oliveira Orsi, Ricardo [UNESP] (Elsevier, 2016)
In this study, samples of coffee honey produced in Espírito Santo State, Brazil, were characterized based on their melissopalynology, physicochemical and nutritional properties, and mineral and caffeine contents. The caffeine content in the nectar from coffee flowers was measured by high performance liquid chromatography (HPLC). Blends of honey were obtained from three Coffea arabica crops, each with 10 colonies of Africanized Apis mellifera. All honey samples contained monofloral (75-78%) pollen belonging to C. arabica. Physicochemical parameters (total acidity, pH, moisture, dry matter, ash, and qualitative hydroxymethylfurfural) were within the approved limits established by EU legislation. Coffee honey contains high levels of ascorbic acid (294.68 mg kg-1) and low amounts of total flavonoids (3.51 ± 0.18 mg QE kg-1). The most abundant minerals were potassium and calcium (962.59 ± 154.3 and 343.75 ± 25.56 mg kg-1, respectively). The caffeine content in coffee nectar (1.64 mg kg-1) was approximately 8-fold lower than that in honey (12.02 ± 0.81 mg kg-1).
Keywords: Apis mellifera; Caffeine; Coffea arabica; Quality